Fructo-oligosaccharides lower serum lipid levels and suppress high-fat/high-sugar diet-induced inflammation by elevating serum and gut levels of short-chain fatty acids. Issue 4 (October 2020) - Yu, Renqiang; Yin, Yongxiang; Cao, Minkai; Ye, Danni; Zhang, Yinghui; Zhou, Qin; Mei, Yingzi
Objective: This study aimed to investigate the effects of fructo-oligosaccharides (FOS) on serum lipid levels and to determine the mechanisms underlying these effects and the potential role of inflammation. Methods: Male C57BL/6 mice received a normal diet, a high-fat/high-sugar (HFS) diet, or an HFS diet supplemented with 10% FOS for 10 weeks. In vivo intestinal and serum short-chain fatty acid (SCFA) levels were measured by gas chromatography. In vivo serum levels of alanine transaminase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), 8-hydroxy-2'-deoxyguanosine (8-OHdG), and malonaldehyde (MDA) were also measured. Lipid accumulation was visualized. Reactive oxygen species (ROS) generation was evaluated and apoptosis was quantified. Results: FOS reversed in vivo HFS-induced lipid accumulation in the liver. An HFS diet increased ALT, AST, TC, TG, and LDL serum levels, decreased HDL serum levels, and increased IL-6, TNF-α, 8-OHdG, and MDA levels. These changes were reduced by FOS. FOS also increased intestinal and serum levels of short chain fatty acids (SCFAs). In vitro, SCFAs ameliorated palmitic acid-induced ROS production and apoptosis of HepG2 cells. Conclusion: FOS supplementation lowers serum lipid levels and ameliorates HFS-induced inflammation by upregulating SCFAs.